(untitled) (Bangladesh Journal of Animal Science, 2016)
Twenty pregnant ewes were used in this study. Ten pregnant ewes with a mean live weight of 19.37 Kg ±0.87 served as the control animals, the others with an average live weight of 19.50 Kg ± 0.37 were starved for 7 days to study the reproductive performances, feed intake and appetite, body weight and rate of recovery in the animals. Test animals were starved during the first week of the last trimester of pregnancy (16th week). Starvation did not cause any significant changes in gestation length, which was within the normal range of 146 to 149 days. A live weight loss of 3.20% was observed during the starvation period. As the starvation progressed, the animals became weak and dull in appearance. Their hairs became loose and tended to fall out. Moreover, as from the 5th day of starvation, they were in a semi-comatose condition and were observed to sway when made to walk. Starvation also resulted in lower (P<0.05) birth weight of lambs:2.05 ± 0.05 kg for lambs from starved ewes compared to 2.25 + 0.10 Kg for lambs from the control pregnant ewes. However, subsequent growth of all lambs produced during the study was not appreciably affected. On resumption of ad libitum feeding appetites as Dry matter intake was low and erratic for 4-6 days. There after feed intake returned to normal with a marked increase in live weight gain. Bang. J. Anim. Sci. 2016. 45 (2): 35-40